Identification of Livestock Characteristics for Selling Price Determination of Buffaloes in Sumbang Village, Curio Sub district, Enrekang District - Busrayana Busrayana; A. Asnawi; S. N. Sirajuddin (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
This study aimed to identify the characteristics and selling price of livestock as well as characteristics of buffaloes which determine the selling price in Sumbang Village, Curio Sub district, Enrekang District. The type of study was descriptive using the snowball method in determining the number of samples.Descriptive analysis was used to identify the characteristics of buffaloes in relation to their selling price. The results of study indicated that the characteristics of buffaloes were determined according to the horns, feathers whirl position, skin color, feather color and physical conditions. These characteristics would dictate the selling price of the buffaloes, whichranged between IDR.12,000,000.- and IDR. 53,000,000.-.